SISTEM INFORMASI PENGOLAHAN DATA SURAT PERINTAH PERJALANAN DINAS (SPPD) PADA KANTOR DINAS LINGKUNGAN HIDUP KABUPATEN MUARO JAMBI DENGAN MENGGUNAKAN PROGRAM VISUAL BASIC 6.0: Travel Service Order Letter, Microsoft Visual Basic 6.0, SQL - -, Mulyadi (LP2M Universitas Nurdin Hamzah, 2017)
The problem with the number of employees who are quite a lot and with the manufacture of SPPD is still very inefficient because at any time employees are assigned to do the Service out suddenly and the operator must look for one by one employee data and also takes time to look for it. Along with the development of information and communication technology (ICT) which has great influence for changes in all areas, including in the field of Office, especially in the process of making SPPD called SPPD electronics or based on computer-based SPPD system that aims to facilitate in generating information , simplify the data search and report generation. In order to produce quality information, the quality in question is judged from the accuracy, timeliness and simplify the employee in the case of making Travel Service License (SPPD).